Design of an Electronic Healthcare Record Server Based on Part 1 of ISO EN 13606. Issue 2 (29th June 2011) - Austin, Tony; Lim, Yin Yu; Nguyen, David; Kalra, Dipak
Abstract : ISO EN 13606 is a newly approved standard at European and ISO levels for the meaningful exchange of clinical information between systems. Although conceived as an inter-operability standard to which existing electronic health record (EHR) systems will transform legacy data, the requirements met and architectural approach reflected in this standard also make it a good candidate for the internal architecture of an EHR server. The authors have built such a server for the storage of healthcare records and demonstrated that it is possible to use ISO EN 13606 part 1 as the basis of an internal system architecture. The development of the system and some of the applications of the server are described in this paper. It is the first known operational implementation of the standard as an EHR system.